A Note on Pattern Knife for Evaluation of Turning Qualities of Timbers - Jaitly, V. P.; Singh, Avtar; Pant, B. C. (Indian Forester, 1985)
Wood turning is mainly done by using conventional hand tools by the skilled and specialized wood turners. The performance of profiled wood turning knife fabricated recently indicated that these are exceptionally good in their performance. The operation of turning becomes very fast and thus energy is saved. The time lost in repeated measurements by the turner is at all eliminated. The time is thus also saved. The overall turning operation becomes very quick and simple. Development of a variety of such pattern knives for various wooden turnery items needs attention for their batch production. The process requiries no skilled wood turners which is inevitable in conventional hand turning.